Agresi dan Kejahatan Terhadap Perdamaian - Thalis Noor (UIN Sunan Kalijaga Yogyakarta, 2014)
The defining of aggression and the penal responsibility should be able to bearranged, both based on the London Agreement and the Draft Code of Crime ofAgainst and Security of Mankind. But because the super power states have egoism sothat they still will act aggression in the name of self defense right. The issues ofterrorism, communism ideology and radicalism always will be reasoning of self defense tooffense and attack another states and then to upset peace rights. Economic interesting todeveloping countries natural resources is a main motivation of self defense.